Erosion of sand screens by solid particles: a review of experimental investigations - Abduljabbar, A. (Springer Science and Business Media Deutschland GmbH, 2022)
In oil and gas industry, sand can be carried with oil and gas, when producing from unconsolidated sandstone reservoirs. The existence of sand particles with fluids flow can lead to severe damages to production systemâs components. Therefore, sand control techniques are needed to prevent potential damages. Standalone sand screens (SAS) are widely used because they can provide reliable sand control with low cost and low complexity. However, SAS application can become disadvantageous because of mechanical erosion due to sand particle impingement. The experimental investigation of sand screens erosion is challenging, as the measurements are to be carried out for a representative SAS material and geometry at laboratory-scale simulated conditions. The simulated conditions should mimic the real flow conditions, which involve many interrelated parameters. Some of these parameters are related to the entrained sand particles (i.e., particle shape, size and, concentration) while other parameters are related to the flow characteristics (i.e., flow velocity and fluid properties). In this review, the key factors influencing sand screens erosion are described, and erosion mechanisms are highlighted. In addition, experimental results showing the effects of key parameters on SAS erosion are discussed and evaluated. Also, challenges associated with previous studies, along with a proposed outlook to overcome those challenges, are presented. It has been found that the limitations of the previous studies are related to test setup and flow direction, particleâparticle interaction, and particleâfluid interaction considerations. This review highlighted noticeable research gaps in sand screens erosion measurements that can be considered in future. Â© 2022, The Author(s).